DETERMINING THE DAMPING FACTOR OF THE RULER IN WATER USING LOGGER PRO - Silaban, Berkatdo; Panuluh, Albertus Hariwangsa; Silaban, Bajongga (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the value of the damping coefficient in water for a ruler using three types of materials and two different oscillation directions. The research problem is how the damping coefficient of several types of solids oscillates in water. The type of oscillating solid is a ruler whose materials are made of aluminum, iron, and stainless steel with varying lengths and widths . The research method used is an experiment with a water sample at a temperature of 200C with a viscosity value of 1,00 mPa.s found in the faucet of the physics laboratory of the University of Sanata Dharma Yogyakarta. The data collection tool used is Video Logger Pro, which is considered to be accurate in measuring attenuation for each time it makes observations on each type of solid. Based on the results of the study by swinging the ruler in different oscillation modes at a declination angle of < 10 0, with variations in length being cut 9,5 cm, then each of them was cut back twice with the next 2 cm in length, creating three variations in length. Cut the width variation from the initial 2,6cm wide, then cut the next 0,3cm width twice so there are three width variations. Based on the results of the study, it was found that the smaller the moment of inertia, the smaller the value of the damping coefficient